Promotion Strategies for BMT to Enhance Competitive Advantage: A SWOT Analysis - Abdullah Ahadish Shamad Muis (PT. Islamic Research Publisher, 2023)
This article delves into the realm of promotion strategies for Baitul Maal wat Tamwil (BMT) aiming to enhance their competitive advantage. To achieve this goal, the study employs a SWOT analysis, evaluating the organization's Strengths, Weaknesses, Opportunities, and Threats. This research focuses on BMT Kedinding Surabaya, collecting data from both internal and external sources. The findings of this study reveal that BMT Kedinding Surabaya has implemented five promotional mix elements. By identifying internal and external factors, this research provides insights into crafting effective promotion strategies tailored to the unique characteristics and challenges faced by BMT. As a result, we recommend that BMT Kedinding Surabaya pursue an aggressive promotion strategy, as they have greater opportunities and strengths, with the hope of maximizing the existing opportunities to enhance their competitive edge. Ultimately, the research provides valuable guidance for BMT’s seeking to prosper in the increasingly competitive financial landscape while adhering to Islamic principles.